The McGraw-Hill guide writing for college, writing for life - Roen, Duane; Maid, Barry M.; Rankins-Robertson, Sherry 1976- (New York McGraw Hill LLC, 2022)
The McGraw-Hill Guide to Writing is designed to help students learn to write more effectively not only in their college courses but also in their professional, civic, and personal lives. Combining a flexible reader, rhetoric, research guide, and handbook, The McGraw-Hill Guide shows students how to set goals for their writing, to use effective composing strategies to reach those goals, and to assess their progress toward achieving them. Based on the idea that effective writers are strong communicators in any context, The McGraw-Hill Guide to Writing emphasizes the skills established by the Writing Program Administrator's Outcomes Statement that form the foundation of assessment practices at writing programs throughout the country -- rhetorical knowledge, critical thinking, writing processes, and conventions. These skills form the basis of the instruction in each assignment chapter and throughout the text. - Provided by publisher.
Includes index.
Keywords: English language -- Rhetoric. -- Handbooks, manuals, etc